Polyphasic Characterization of a Potential Novel Cellulolytic Bacterium Brevibacillus Brevis Strain St-2 - Prasad, P.; Singh, Tanuja; Bedi, S. (JOURNAL OF ADVANCES IN BIOTECHNOLOGY, 2014)
The tremendous commercial potential of cellulases in a variety of applications remains the driving force for research in this area. The present study was aimed at isolation and screening of promising cellulolytic strains from locally collected soil samples. A promising cellulose degrading bacterial strain designated as St-2 was isolated from agricultural field. Optimization of fermentation media ingredients and environmental factors were done for optimizing growth of the strain which facilitates effective cellulase production. St-2 showed luxuriant growth on sucrose, lactose, mannitol and inositol whereas the growth was moderate on dextrose and fructose. The strain was able to grow in a wide range of pH (5-11) and temperature (4-45 C) and was tolerant to up to 6% (w/v) of NaCl concentration in the medium. The results indicate wide spectrum adaptability of the strain to variable pH, temperatures and saline concentrations that makes it an advantageous organism to survive in the fluctuating environmental conditions. The optimum pH and temperature for enzyme production were 7 (with 2.11 U/ml CMCase activities and 2.22 U/ml FPase activities) and 37C (with 1.73 U/ml CMCase activities and 1.92 U/ml FPase activities), respectively. The morphological and biochemical characteristics of the strain were consistent with those of the genus Brevibacillus. Analysis of the 16S rRNA gene sequence of strain St-2 showed a similarity score of 99% with Brevibacillusbrevis(GeneBank Accession No. AB271756) having BLAST score ranging between 821 to 827 bits.